Real Performance Evaluation On MQTT and COAP Protocol in Ubiquitous Network Robot Platform (UNRPF) for Disaster Multi-robot Communication - Yamin, Muhammad Ikrar; Kuswadi, Son; Sukaridhoto, Sritrusta (EMITTER International Journal of Engineering Technology, 2018)
Disaster multi-robot has a significant role in a disaster area to do many tasks like detection of fire, search and rescue of victims, etc. It needs to build good communication between the operator and multi-robot and among multi-robot themselves to perform their tasks quickly and efficiently. This relates with the queue message protocol system. In this research, we implemented the queue message protocol on mesh topology and integrated it on the robot platform. Recently, development of IoT (Internet of Things) Technology causes development of communication protocol. MQTT and CoAP are among the communication protocols used for IoT needs.  Both  protocols performance were compared when  used and implemented into disaster multi-robot. We also integrated MQTT protocol and robot  platform python based (UNR-PF). The result shows that MQTT protocol is easier to be  implemented on to disaster multi-robot platform (UNR-PF) on mesh topology than CoAP, and that data transfer rate of MQTT protocol has data transfer rate higher than CoAP.